2023
DOI: 10.1186/s12967-022-03857-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between radiotherapy and risk of second primary malignancies in patients with resectable lung cancer: a population-based study

Abstract: Background The most common form of treatment for non-metastatic lung cancer is surgery-based combination therapy, which may also include adjuvant radiotherapy or chemotherapy. Second primary malignancies (SPMs) are uncommon but significant radiation side effects in patients with resectable lung cancer, and SPMs have not been adequately investigated. Our study aims to assess the correlations of radiotherapy with the development of SPMs in patients with resectable lung cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Mediastinal radiation therapy has the potential to cause harm to irradiated organs, leading to acute or chronic side effects, such as radiation pneumonitis, chronic pulmonary fibrosis, pericarditis, congestive heart failure, myocardial infarction, and valvular heart disease, [19][20][21][22][23] and even the development of radiationinduced secondary malignancies. [24,25] Guidelines developed by Ontario Health (Cancer Care Ontario)'s Program in Evidence-Based Care in collaboration with the Lung Cancer Disease Site Group have concluded that PORT does not yield satisfactory outcomes for patients with Masaoka-Koga stage II thymomas. Due to the potential risk of radiation toxicity, the Working Group does not routinely recommend PORT therapy for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal radiation therapy has the potential to cause harm to irradiated organs, leading to acute or chronic side effects, such as radiation pneumonitis, chronic pulmonary fibrosis, pericarditis, congestive heart failure, myocardial infarction, and valvular heart disease, [19][20][21][22][23] and even the development of radiationinduced secondary malignancies. [24,25] Guidelines developed by Ontario Health (Cancer Care Ontario)'s Program in Evidence-Based Care in collaboration with the Lung Cancer Disease Site Group have concluded that PORT does not yield satisfactory outcomes for patients with Masaoka-Koga stage II thymomas. Due to the potential risk of radiation toxicity, the Working Group does not routinely recommend PORT therapy for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has one of the highest fatality rates among malignant tumors in China ( 21 , 22 ). Compared with small cell lung cancer, NSCLC has a slow onset and growth rate but is generally found to be in an advanced stage at initial diagnosis and, therefore, very difficult to control and treat ( 23 - 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 Nowadays, with the prevalence of low-dose computed tomography (LDCT), 4 a significantly greater number of patients with multiple indeterminate pulmonary nodules (IPNs) has been identified, most of which are recognized as multiple primary lung cancer (MPLC). 5 , 6 , 7 A subset of these patients is found to have a large number of lesions at the time of diagnosis, such as around ten or even dozens. These special cases are referred to as ‘super MPLC’.…”
Section: Introductionmentioning
confidence: 99%